Predicting the impact of COVID-19 on fertility in the Special Region of Yogyakarta, Indonesia - Alfana Muhammad Arif Fahrudin; Rohmah Hidayati Nur; Nurulhuda Salma; Sadali Mohammad Isnaini (E3S Web of Conferences, 2021)
The aim of this research is to explain the predicted impact of Covid-19 on fertility in the Special Region of Yogyakarta (DIY). The indicators used are the number of pregnancies and the number of births. To get pregnancy and birth predictions, various basic data were processed using the Spectrum program using the DemProj and Famplan modules, then analyzed by descriptive analysis. The basic data is collected from the Central Statistics Agency (BPS) and other relevant agencies. The result shows that birth and pregnancies in DIY will increase. This prediction is based on the decreasing use of short -term contraceptive methods during the pandemic. In the worst-case scenario, the rise in pregnancies between 2019-2020 would be 67,862 cases, meanwhile births are expected to increase by 37.56 thousand cases during the same period.